Can cryptocurrencies be the future of money? The role of democracy - Mehmet Baha Karan (The Central European Review of Economics and Management (CEREM), 2022)
The purpose of this article is to evaluate if cryptocurrencies that have robust technology and anonymous features can be the money of the future. In this study, the transition phases of paper money, which started to be used at the beginning of the 17th century, to bank money, then banknotes and fiat money were examined. By pointing out that the fiat money system has developed within the conditions of humanity's search for democracy and freedom. It has been stated that fiat money can only be successful in democratic systems where institutions operate freely, and therefore fiat money is an instrument of democracy. It has been concluded that the authoritarian tendencies, which have started in the world since the 21st century due to nationalism, migration, and climate change, are an important factor in the widespread use of cryptocurrencies. It has been concluded that the spread of cryptocurrencies is directly dependent on the democratic practices of countries and if authoritarianism rises, the use of cryptocurrencies will inevitably be more.
Keywords: E50; D02; 330; cryptocurrencies; fiat money; democracy